Hubungan Antara Tingkat Pendidikan dan Pengetahuan Gizi Ibu dengan Status Gizi Murid Sekolah Dasar Desa Leinitu dan Desa Nalahia Kecamatan Nusalaut - Tualepe, Hatibansa H; Augustyn, Gelora H; Tetelepta, Gilian (Jurnal Agrosilvopasture-Tech, 2023)
Development in the health sector is part of national development which aims to build awareness and the ability to live a healthy life for everyone in order to realize a better degree of public health. Nutritional problems that affect health are everywhere, and the four factors that cause nutritional problems are the economy, sanitation, parents' education, and parents' lifestyle. Nutritional status is the condition of a person's body as a result of the food consumed. Children as national assets that will continue the development of the nation and state must have good nutritional status. For this reason, knowledge and knowledge of maternal nutrition is important in choosing food for consumption by children. Nalahia and Leinitu Village. The selection of respondents was carried out by simple random sampling of 15 respondents from each village. After that, the number of respondents is 30 children. The results showed that the nutritional status of respondents according to BMI in Leinitu Village was 80% normal, 20% thin in Nalahia Village 86.66% normal, 6.66% thin, and 6.66% fat. Leinitu Village Mother's Education Elementary 26.66%, Middle School 20%, High School 40%, D3/S1 13.33%, Nalahia Village Middle School 20%, High School 66.67%, Bachelor Degree 13.33%. Nutrition Knowledge of Leinitu Village Mothers Good 86.66%, 13.33% poor, Nalahia Village 93.33% good and 6.67% poor. The results showed that there was no effect of a mother's education on nutritional status in Leinitu village, while for Nalahia village there was a significant relationship. There was no significant relationship between the mother's nutritional knowledge and the nutritional status of respondents in the two villages